Influences of Nanosilica Particles on Density, Mechanical, and Tribological Properties of Sisal/Hemp Hybrid Nanocomposite - K. Dhanasekar; A. Mohana Krishnan; Gopal Kaliyaperumal; Melvin Victor De Poures; P. Chandramohan; N. Parthipan; C. B. Priya; R. Venkatesh; Kassu Negash (Advances in Polymer Technology)
Focusing on natural fibers are the prominent substitution for synthetic fiber and reinforced into polymer matrices found unique properties such as lightweight, cost-effectiveness, and good mechanical and wear properties. Incompatibility and low adhesive behavior are the primary drawbacks found during the fabrication of natural fiber-bonded polymer matrix composites. The constant weight percentage (10 wt%) of sisal and hemp fiber is treated with a 5% NaOH solution for improving adhesive behavior and bonded with epoxy. The prepared sisal/hemp/epoxy combination is blended with 0 wt%, 3 wt%, 6 wt%, and 9 wt% silica nanoparticles, which results in reduced voids (1.32%) and increased flexural strength (56.98 MPa). Based on the compositions of fiber and reinforcement, the density of the composite varied. Samples 3-6 wt% of silica nanoparticle-blend sisal/hemp/epoxy composite offered maximum tensile and impact strength of 52.16 MPa and 2.1 J. An optical microscope analyzed the tensile fracture surface, and the failure nature was reported. The dry sliding wear performance of composite samples is tested by pin-on-disc setup with a 10 N-40 N load of 10 N interval at 0.75 m/sec. Sample 3 found good wear resistance compared to others.